2017
DOI: 10.20431/2454-6380.0303003
|View full text |Cite
|
Sign up to set email alerts
|

Why do University Students Enroll in Physical Activity Education Courses? Differential Affects of Required Versus Elective Institutional Policies

Abstract: Abstract:The aims of this study were to determine university students '

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Students also enrolled in physical education classes for various reasons (i.e., general, physical, mental, social, and academic), and it was found that a greater number of females enrolled in fitness classes, whereas a greater proportion of males enrolled in sports courses (Lackman et al, 2015). Additionally, Kim and Cardinal (2017) claimed that college and university students attend physical activity classes primarily to improve their fitness and to exercise regularly. However, Cosic et al (2018) indicated that females have less engagement in physical activity than males.…”
Section: Introductionmentioning
confidence: 99%
“…Students also enrolled in physical education classes for various reasons (i.e., general, physical, mental, social, and academic), and it was found that a greater number of females enrolled in fitness classes, whereas a greater proportion of males enrolled in sports courses (Lackman et al, 2015). Additionally, Kim and Cardinal (2017) claimed that college and university students attend physical activity classes primarily to improve their fitness and to exercise regularly. However, Cosic et al (2018) indicated that females have less engagement in physical activity than males.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several research studies conducted in Europe reported low PA levels among Romanian (Fagaras et al, 2015), Polish (Podstawski et al, 2014) and Spanish (Martinez-Lemos et al, 2012) students. Supplementary evidence suggests that many UCS do not meet the above recommendations in the process of transitioning from adolescence to adulthood (Kim & Cardinal, 2017;Sigmundova et al, 2013). University students who begin to live independently experience changes in lifestyle habits, attitudes and social roles.…”
Section: Introductionmentioning
confidence: 99%